Introduction: Bruno Latour's Influence on the Study of Religion - Robertson, David G. (Implicit religion, 2023)
Introduction to the special issue, "Bruno Latour and the Study of Religion" by the editors. It first sets out Latour’s career, its major themes and most significant publications. It then describes three "vectors" of his influence on the study of religion - Actor- Network Theory and other network- based approaches, relocating agency beyond the human; his "Catholic" approach to religion, decentring traditional narratives on "belief" and "transcendence" and instead presenting religion as a "mode of existence"; and, finally, his critique of the critical project itself. The article also includes descriptions of each of the contributions to the special issue.